Implementasi Algoritma LUC Dalam Penyandian Teks - Ramadani, Dewi (MEANS (Media Informasi Analisa dan Sistem), 2018)
Confidentiality and data security are very important in data communication, both for the purpose of shared security and for individual privacy. Computer users who want the data to be unknown by unauthorized parties always try to get around the way to secure the information that will be communicated or to be stored. One method for securing data or information is cryptographic methods. The LUC algorithm is a cryptographic method using two different keys in the cryptosystem. To encrypt text, an encryption function is used that uses a public key, the result of encryption is encrypted text that is safe from intruders. Furthermore, by decrypting encrypted text using the decryption function using the private key it will return the same text as the original. With the LUC algorithm the author tries to create a text encoding to secure data with the LUC algorithm.